2022
DOI: 10.1093/infdis/jiac201
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Burden of Respiratory Syncytial Virus and Health Care Utilization Among United States Infants Younger Than 1 Year

Abstract: Background The burden and health care utilization (HCU) of respiratory syncytial virus (RSV) in US infants aged <1 year across health care settings are not well characterized. Methods We systematically reviewed studies of RSV and bronchiolitis published 2000–2021 (data years, 1979–2020). Outcomes included RSV hospitalization (RSVH)/bronchiolitis hospitalization rates, emergency department (ED)/outpatient (OP) visit rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…RSV LRTI is widely understood as a seasonal disease that drives infant healthcare visits across all settings. Nevertheless, a systematic literature review of the burden and healthcare utilization associated with infant RSV infections revealed an absence of national emergency department (ED) or outpatient (OP) assessments [ 16 ]. When data were available from across settings, RSV testing frequency was higher in the hospital inpatient (IP) setting than in the ED or OP settings [ 17 , 18 ] and higher among younger patients [ 19 ].…”
Section: Morbidity: Epidemiology and Burden Of Rsvmentioning
confidence: 99%
“…RSV LRTI is widely understood as a seasonal disease that drives infant healthcare visits across all settings. Nevertheless, a systematic literature review of the burden and healthcare utilization associated with infant RSV infections revealed an absence of national emergency department (ED) or outpatient (OP) assessments [ 16 ]. When data were available from across settings, RSV testing frequency was higher in the hospital inpatient (IP) setting than in the ED or OP settings [ 17 , 18 ] and higher among younger patients [ 19 ].…”
Section: Morbidity: Epidemiology and Burden Of Rsvmentioning
confidence: 99%
“…A systematic literature review [ 3 ] of the RSV literature published between January 2000 and June 2021 recently identified 4 publications [ 4–7 ] that reported leading-cause analyses of infant hospitalizations in the US with 1 study conducted in California [ 7 ]. In these studies, RSV bronchiolitis ( International Classification of Diseases, Ninth Revision [ ICD-9 ] code 446.11) was consistently the leading cause of infant hospitalizations; however, all 4 publications [ 4–7 ] utilized data from before 2003, and only 1 study [ 5 ] provided leading-cause analyses by race/ethnicity (US general infant population and American Indian/Alaska Native [AI/AN] infants).…”
mentioning
confidence: 99%
“…This retrospective study is based on the most recent, largest publicly available all-payer databases in the US to describe infant RSV and bronchiolitis burden, rates, and HCU in inpatient hospital and ED settings. To our knowledge, this is the first study since 2000 to provide infant RSV epidemiology data for the ED setting based on nationally representative data [ 7 ]. We found that infant RSVH rates have remained stable over time, whereas RSV ED visit rates have increased.…”
Section: Discussionmentioning
confidence: 99%
“…Palivizumab is recommended for select populations, that is, premature infants born ≤28 weeks’ gestational age (wGA), or those with chronic lung disease of prematurity (CLD) or hemodynamically significant congenital heart disease ( hs -CHD) [ 6 ]. Because palivizumab is the only available option, it is not surprising that the literature is focused on populations who are currently or formerly eligible to receive palivizumab (eg, infants born 29–34 wGA) [ 7 ]. For the broader groups of infants including late preterm to full term and those without comorbid conditions, RSV epidemiology data are limited, and there are no immunization options available [ 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation